Cost‐effectiveness of revascularization in patients with intermittent claudication. Issue 13 (25th October 2018) - Djerf, H.; Falkenberg, M.; Jivegård, L.; Lindgren, H.; Svensson, M.; Nordanstig, J.
Abstract : Background: Revascularization is a treatment option for patients with intermittent claudication. However, there is a lack of evidence to support its long‐term benefits and cost‐effectiveness. The aim of this study was to compare the cost‐effectiveness of revascularization and best medical therapy (BMT) with that of BMT alone. Methods: Data were used from the IRONIC (Invasive Revascularization Or Not in Intermittent Claudication) RCT where consecutive patients with mild‐to‐severe intermittent claudication owing to aortoiliac or femoropopliteal disease were allocated to either BMT alone (including a structured, non‐supervised exercise programme) or to revascularization together with BMT. Inpatient and outpatient costs were obtained prospectively over 24 months of follow‐up. Mean improvement in quality‐adjusted life‐years (QALYs) was calculated based on responses to the EuroQol Five Dimensions EQ‐5D‐3 L™ questionnaire. Cost‐effectiveness was assessed as the cost per QALY gained. Results: A total of 158 patients were randomized, 79 to each group. The mean cost per patient in the BMT group was €1901, whereas it was €8280 in the group treated with revascularization in addition to BMT, with a cost difference of €6379 (95 per cent c.i. €4229 to 8728) per patient. Revascularization in addition to BMT resulted in a mean gain in QALYs of 0·16 (95 per cent c.i. 0·06 to 0·24) per patient, giving an incremental cost‐effectiveness ratio of €42 881 per QALY. Conclusion: The costs associated with revascularization together with BMT in patients with intermittent claudication were about four times higher than those of BMT alone. The incremental cost‐effectiveness ratio of revascularization was within the accepted threshold for public willingness to pay according to the Swedish National Guidelines, but exceeded that of the UK National Institute for Health and Care Excellence guidelines. Abstract : Revascularization effective but pricey